Development of Smart Kit Rainwater Harvesting System for Potable Water Purpose - Sunar, N. M.; Kosat, A. T.; Harun, H.; Hamid, N. H. A.; Khalid, A.; Zaidi, E.; Azhar, A. T. S. (International Journal of Engineering and Technology, 2018)
The Smart Kit Rainwater Harvesting (RWH) system has the potential to contribute to the conservation of clean water usage. The aim of this study is to build an affordable rainwater storage system for all type houses with easy installation and friendly user. The current constraints on the installation of rainwater storage system in the market requires a fairly expensive cost, and skilled technical workers to install it. In contrast, the Smart Kit RWH, is friendly built in a complete set that is easy to install and easy to maintain by homeowners. This system is very suitable for the use in agriculture and farming. This Smart Kit RWH consist of water storage tank, existing gutter and main pipe, first flush diverter and some connector pipe to create this complete system. This product is limited to storing untreated rain water quality, and the quality of rainwater collected can be used as water storage for household and sanitary equipment such as flushing cistern and other potable water usage. Nevertheless, this contributes to the good and the benefits of individuals, communities and nations. This product able to help the rural population in particular of having problems in getting clean water. Hopefully, with the production of this system, it can foster the public's awareness of the advantages and benefits of installing rainwater storage systems at home, plantation and farming.